Effect of Cultural Practices on Growth and Yield of Weedy Rice and Direct Seeded Rice Population in Malwatta Region of AmparaDistrict in SriLanka. - Risva, A.S.M.; Iqbal, Y.B.; De Silva, C.S. (University of Jaffna, 2020)
Weedy rice (WR) (Oryza sativa f. spontanea)was first reported in 1990 and it is occurring with varying population densities in all agro-ecological zones in Sri Lanka. Location field trial was conducted on rice field in Malwatta area during May to August 2018 in Yala season to study the effect of cultural practices on growth and yield ofweedy rice and direct seeded rice (Oryza sativa)(AT362). Seven rice farmers having one rice field per farmer, F1, F2, F3, F4, F5, F6 and F7 from7 different sampling sites were selected for this study. Preliminary Study of the infestation of weedy rice was con ducted The sites were selected on the basis of previous observations of the infestation of weedy rice. It was noted that those farmers followed different cultural practices from land preparation until harvesting. Information on the cultural practices followed by the farmers was recorded on a regular basis by individual contact. Samples were observed and collected from seven rice fields at least 300m distance between plot and at least 50m between from each sample collection point from each location. Sampling points were noted as S1, S2, S3. Samples were collected in 3 different stages as seedling stage, flowering stage and maturity stage. Samples were randomly taken by using 1 x 1m quadratic frame randomly in the selected field. Di ferent types of 2 f samples collected in different stages found within the frame have carefully counted and uprooted from each throw. bags were brought to the laboratory to evaluate the population, plant height, number of tillers, number of panicles, panicles height, number of spikelets per panicle, number of grain within 1 m and yield within 1 m . 2 2 The collected data were analyzed statistically and mean differences among the yield and different farmers under different growth stages were adjudged as per Duncan's Multiple Range Test (DMRT) at 5% level of significance. The result of this survey shows that, the source of seed paddy and cultural practices applied by the farmers in different growth stages impact on the weedy rice population and this leads to impact on growth and yield of direct seeded rice in the selected area. This experiment determined the effective control of weedy rice cannot be based on one single practice, but should rely on a complex management programme based on an appropriate combination of preventative, cultural, mechanical, chemical and genetic means.
Keywords: Cultivated rice.; Growth; Yield; Weedy rice